Bloom’s Taxonomy as a Lens to Explore Student Learning of Design Thinking in Software Engineering Education and Training - Rodrigues, Eriky; Silva, Nabson; Meireles, Maria; Maldonado, José Carlos; Lima, Márcia; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
Background: Design Thinking (DT) has been widely adopted in Software Engineering (SE) for its emphasis on creativity, user understanding, and iterative problem-solving. However, in the context of SE Education and Training (SEET), there is a lack of empirical research exploring how students internalize, engage with, and perceive DT-related content. Aims: Our research aims to understand how SE students perceive and internalize DT concepts during their training. Method: We conducted semi-structured interviews with nine students who had previous contact with DT through an SE course. We used Bloom’s Taxonomy as a foundation, as it offers a structured framework to assess the cognitive levels students reach when learning a given topic. This approach allowed us to explore how students process, retain, and apply DT-related knowledge. We analyzed the data using Grounded Theory procedures. Results: Analyzing through the lens of Bloom’s framework, we found individual differences in the depth of learning and consolidation of DT concepts. Three participants demonstrated analysis-level abilities, four reached the synthesis level, and two attained evaluation-level skills. Our findings also reveal that students associate DT with creativity, user understanding, freedom to explore options, and goal orientation. They also recognized the value of DT techniques for organizing data, guiding technical decisions, and supporting the software development process. Based on our findings, we propose an empirically-based conceptual model that structures students’ perspectives on the use of the DT in SE. Conclusions: We hope our contributions can assist educators in developing strategies to help students better retain DT content, with emphasis on SEET, as our results offer a structured understanding of how students internalize DT in SE.